A Cross-Sectional Study Examined the use of Transvaginal Ultrasound in Assessing Endometrial Cancer in Postmenopausal Women - Kalsoom Nawab, Fauzia Afridi, Mehmood Akhtar Khattak, Hina Gul, Naheed Khan, Irsa Shoaib (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: to determine how successfully transvaginal ultrasonography can be used to identify endometrial cancer in postmenopausal bleeding patients.. Methods: The Khyber Teaching Hospital Peshawar Radiology department performed this cross-sectional study from January 2015 to January 2016. TV-tested endometrial-thickness women were included. The endometrial cavity was examined colonially and sagittal from the internal Os to the fundus. D&C transmitted biopsy samples to the hospital pathology lab for histopathology and TVS comparison. A preform had all this info. Spss 26 analyzed data. Results: The patients’ average age was 64.82 + 07.84 years. On average, menopause lasted 10.45 07.73 years. When endometrial thickness was assessed with tvs, the average thickness was 05.564.26 mm; 45 (32.8%) of the ladies did not have an endometrial thickness of 04 mm. Histopathological examination of endometrial cancer revealed ninety four (66.5%) females with the disease and forty six (32.8%) without. The sensitivity, specificity, npv, ppv, and diagnostic accuracy of tvs were determined to be [93.1%], [86.5%], [91.4%], [94.6%], and [93.6%], respectively. Conclusion: According to the study’s results, tvs is an effective diagnostic tool for ruling out postmenopausal hemorrhage and sparing patients from intrusive treatments. Keywords: Transvaginal ultrasonography, endometrial carcinoma, diagnosis, accuracy, positive-predictive-value, negative predictive value